Power, ethics, and ecology in Jewish late antiquity: rabbinic responses to drought and disaster - Belser, Julia Watts (Cambridge Univ. Press, 2015)
"Rabbinic tales of drought, disaster, and charismatic holy men illuminate critical questions about power, ethics, and ecology in Jewish late antiquity. Through a sustained reading of the Babylonian Talmud's tractate on fasts in response to drought, this book shows how Bavli Ta'anit challenges Deuteronomy's claim that virtue can assure abundance and that misfortune is an unambiguous sign of divine rebuke. Employing a new method for analyzing lengthy Talmudic narratives, Julia Watts Belser traces complex strands of aggadic dialectic to show how Bavli Ta'anit's redactors articulate a strikingly self-critical theological and ethical discourse. Bavli Ta'anit castigates rabbis for misuse of power, exposing the limits of their perception and critiquing prevailing obsessions with social status. But it also celebrates the possibilities of performative perception - the power of an adroit interpreter to transform events in the world and interpret crisis in a way that draws forth blessing --